Effectiveness of the theory of reinforcement and punishment for engaging students’ towards Arabic vocabulary: case of the Arabiyatuna board game - Abdul Rahim, Abdul Hadi; Noorzamri, Nurul Husna; Wan Shahrudin, Wan Syatirah; Zolmaily, Muhammad Akmal (Everant Publisher p(Ltd), 2025)
This study explores the effectiveness of the “Arabiyatuna” board games as a pedagogical tool for enhancing students' vocabulary acquisition and engagement with the Arabic language and culture. The research was conducted with a sample of 30 students at Universiti Islam Antarabangsa Tuanku Syed Sirajuddin (UniSIRAJ) previously known as Kolej Universiti Islam Perlis (KUIPs) who participated in playing the Arabiyatuna board game sessions designed to introduce and reinforce Arabic vocabulary which involved experimental and control groups. Pre-and-post-intervention assessments were administered to measure the mastery of vocabulary based on the Mecca Common Vocabulary List. The students must observe the instructions in the punishment card as the research adopted the theory of Reinforcement and Punishment to strengthen the students’ memorization of the chosen vocabulary. The result indicates a significant improvement in students' vocabulary acquisition and a heightened interest in Arabic vocabulary. Qualitative feedback from participants also suggests that the interactive and enjoyable nature of board games fosters a positive learning environment, encouraging active participation and sustained interest. These findings support the integration of board games into language learning curricula as an effective strategy for engaging students and enhancing their linguistic and cultural competencies.